Effects of salicylic acid on the growth and pathogenicity of Zymoseptoria tritici - Elham Zamani; Forough Sanjarian; Ebrahim Mohammadi-goltapeh; Naser Safaie (Biological Journal of Microorganism, 2018)
Introduction: Zymoseptoria tritici, is a species of filamentous fungus and causes the widespread wheat disease Septoria tritici blotch (STB). Salicylic acid has a key role in plant defence reactions and is also involved in the induction of systemic acquired resistance. However, the contribution of SA to the interaction of Z. tritici -wheat in STB is not entirely clear.In this study, it was shown that the Z. tritici mycelial growth and conidia germination were significantly inhibited the presence of increasing concentration of SA in both liquid and solid media. In addition, the effect of SA on pathogenicity of Z. tritici in wheat was investigated. Materials and methods: In this study, the inhibitory effect of SA on Z. tritici at different concentrations (1 to 20 mM) in vitro, and also, the efficacy of its exogenous application in the suppression of STB in wheat under the greenhouse condition were investigated. In vitro evaluation was done on YMDA and YMDB to determine the effect of SA on the germination of conidia and growth of mycelium, respectively.  Susceptible bread wheat cultivar was grown in pot and inoculated with fungus spores and SA in a three-leaf stage for green house experiments. Results: The results showed that the germination ofconidia was completely inhibited by 4 mM SA. Furthermore, in modified YMDA plates at over 0.8 mM, the colonies diameter was reduced significantly. The result of in planta assay indicated that the foliar application of 4 mM SA can significantly reduce the disease symptoms on the wheat leaves. Discussion and conclusion: Regarding our data, it seems that SA shows more inhibitory effect in in vitro experiments than in planta. Moreover, according to the positive effects of SA on STB, the survey results can be considered as a potential approach in the management of this disease.